Bibliometric analysis of sustainable public transport indicators: trends of global research from 2000-2024 - Keblawi, Ala Zuhier; Mohd Hasan, Mohd Rosli; Al-Sahili, Khaled Ahmad; Sadullah, Ahmad Farhan Mohd; Abdulhussein, Samer Saeed (Mustansiriyah University College of Engineering, 2026)
This article offers a bibliographic review of studies undertaken concerning sustainable public transport and the importance of sustainability indicators to the growth of the transport field. The study used a total of 430 Scopus-indexed articles published between the years 2000 and 2024 using the phrases “sustainable,” “public transport,” and “indicators.” These articles were reviewed using the software packages VOSviewer and Biblioshiny. The article explores the contribution of the indicators towards the analysis and implementation of sustainable transport systems, and their added value and limitations. The findings of the article indicate that the leading country concerning the publication of articles is China, and the leading journal is Sustainability (Switzerland). The most used keywords are “indicators,” followed by “transport,” “sustainability,” and “sustainable transport systems.” The most used indicators are emissions, energy consumption, and accessibility, followed by user satisfaction and cost efficiency. These are used concerning the environmental, societal, and economic aspects of the sustainability of the transport systems. The leading nation studied herein is Italy, and there are various studies that highlight the progress of the intelligent and sustainable mobility systems of the Italian States.